Youth tobacco use in South-East Asia: Implications for tobacco epidemic and options for its control in the region - Manju Rani; Thaksaphon Thamarangsi; Naveen Agarwal (Wolters Kluwer Medknow Publications, 2017)
Nearly half of all male population and two in every five females in the WHO South-East Asia Region (SEAR) consume some form of tobacco. Preventing initiation among adolescents is critical for overall tobacco control. We assessed the trends in youth tobacco use and policies in SEAR. Data are used from school-based youth (Global Youth Tobacco Survey and global school student-based health survey) and adult (Global Adult Tobacco Survey, STEPS) tobacco surveys and the WHO Framework of Convention of Tobacco Control (FCTC) implementation database. More than 10% of 13-15-year-old adolescent students reported tobacco use in 8 out of 11 countries. The prevalence of smokeless tobacco exceeded that of cigarettes except in Indonesia, Thailand, and Timor-Leste. No consistent declining trends in tobacco use were observed in any of the countries with 3 or more data points. More than half of all daily smokers aged 20-34 years initiated "daily" smoking before 20 years of age. 19% (Bangladesh) to 55% (Timor-Leste) of 13-17-year old students tried their first cigarette before their 14th birthday. Majority of adolescent students in most of the SEAR countries reported purchasing their cigarettes from store/shop/vendor and as single sticks, with few exceptions and purchased them as "single" cigarette. There is a limited change in affordability of cigarettes in SEAR over time. Tobacco use remains high among youth in SEAR. Efforts should be strengthened to fully implement/enforce recommended policy measures (legal minimum age, fiscal measures to reduce tobacco affordability; prohibiting sale of single cigarettes, etc.) and to explore new measures (e.g., tobacco-free generation).